Effectiveness of Internships as a Marketing Strategy in Tertiary Courses: The Case of Nanyang Institute of Management Singapore - Johnson, Teo (Digital Repository of Theses, 2024)
The effectiveness of internships as a strategic marketing tool in tertiary courses is examined in this thesis, with a focus on the Nanyang Institute of Management (NIM) in Singapore. Innovative strategies are considered as higher education institutions continually adjust to changing environments to draw and keep students. With the opportunity to gain practical experience in the workplace and enhance one’s academic background, internships have become a popular marketing tactic. The study looks at internship experiences and analyses student enrolment data quantitatively. The study assesses how NIM’s internship programs affect student enrolment by examining the relationship between internship participation and attracting potential students. Also, by examining students’ perspectives and experiences, it explores the qualitative aspects of internships and offers insights into the program is success as a marketing tool. Through surveys and statistical analysis, the study thoroughly explains how internships have impacted learners’ experience in the industry. The research’s conclusive findings offer practical insights for educational institutions, especially NIM, to optimize their internship programs and contribute to the academic discourse surrounding marketing strategies in tertiary education. The findings reveal that internships prepare learners for better employment opportunities in the hospitality industry by enhancing relevant skills, professionalism, and work ethics. Including internship programs at NIM in Singapore is an effective marketing tool. Some reasons that justify this inference include enhanced visibility, brand reputation, and the bridge between education and industry practices.